Characteristics of municipal leadership in Uttar Pradesh - Singh, U.B. (2018)
Municipal elections in Uttar Pradesh have special significance, more so during a changed regime. Fresh elections to municipalities were held in November 2017. The study finds that the newly elected Mayors and Chairpersons are comparatively young and highly educated, but majority is novice to governance. The recent municipal elections were shocker to the entire major political parties, as majority of the local leaders are independent with no political affiliation. The disinterest of people in politicians highlights the interest of people in development and better governance. - Reproduced.
Keywords: Local government; Municipalities